A comprehensive review on recent advancements in biodegradation and sustainable management of biopolymers. (15th August 2022) - Awasthi, Sanjeev Kumar; Kumar, Manish; Kumar, Vinay; Sarsaiya, Surendra; Anerao, Prathmesh; Ghosh, Pooja; Singh, Lal; Liu, Hong; Zhang, Zengqiang; Awasthi, Mukesh Kumar
Abstract: Recent years have seen upsurge in plastic manufacturing and its utilization in various fields, such as, packaging, household goods, medical applications, and beauty products. Due to various adverse impacts imposed by synthetic plastics on the health of living well-being and the environment, the biopolymers have been emerged out an alternative. Although, the biopolymers such as polyhydroxyalkanoates (PHA) are entirely degradable. However, the other polymers, such as poly (lactic acid) (PLA) are only partially degradable and often not biosynthesized. Biodegradation of the polymers using microorganisms is considered an effective bioremediation approach. Biodegradation can be performed in aerobic and anaerobic environments. In this context, the present review discusses the biopolymer production, their persistence in the environment, aerobic biodegradation, anaerobic biodegradation, challenges associated with biodegradation and future perspectives. In addition, this review discusses the advancement in the technologies associated with biopolymer production, biodegradation, and their biodegradation standard in different environmental settings. Furthermore, differences in the degradation condition in the laboratory as well as on-site are discussed. Highlights: Biopolymer biodegradability and its environmental persistence has been discussed. Degradability of oxo-degradable plastics has been discoursed. Biopolymers degradation in the complex environment have been emphasized. Effective and efficient biodegradation standard test methods has been explored. More significant and efficient biodegradation standard test methods are required.